Nikola Pašić and Ante Trumbić the Kingdom of Serbs, Croats and Slovenes - Djokić, Dejan (Haus histories, 2010)
This text will provide parallel biographies of two key Yugoslav politicians of the early 20th century: Nikola Pasic, a Serb, and Ante Trumbic, a Croat. It will also offer a brief history of the creation of Yugoslavia.